2018
DOI: 10.1080/17470218.2017.1350871
|View full text |Cite
|
Sign up to set email alerts
|

Try and try again: Post-error boost of an implicit measure of agency

Abstract: The sense of agency refers to the feeling that we control our actions and, through them, effects in the outside world. Reinforcement learning provides an important theoretical framework for understanding why people choose to make particular actions. Few previous studies have considered how reinforcement and learning might influence the subjective experience of agency over actions and outcomes. In two experiments, participants chose between two action alternatives, which differed in reward probability. Occasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…Despite these straightforward intuitions, the exact relationship between agency and learning from errors has hardly been studied. Intentional binding, one implicit measure of SoA, is stronger in the trial following a loss, than in a trial following a win, constituting a post error agency boost, or PEAB effect (Di Costa et al, 2017). Losses can convey important information regarding the structure of the task (as in probabilistic learning setting), and thus can inform future decisions by helping agents to choose subsequent actions which maximize their rewards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these straightforward intuitions, the exact relationship between agency and learning from errors has hardly been studied. Intentional binding, one implicit measure of SoA, is stronger in the trial following a loss, than in a trial following a win, constituting a post error agency boost, or PEAB effect (Di Costa et al, 2017). Losses can convey important information regarding the structure of the task (as in probabilistic learning setting), and thus can inform future decisions by helping agents to choose subsequent actions which maximize their rewards.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Di Costa, Théro, Chambon, & Haggard (2017) used the probabilistic reversal learning paradigm (PRL) to address the link between learning an agency. The task required participants to choose between pressing one of two keys, each mapped to a different monetary reward probability (80:20).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we also included a ‘predictability’ factor in the coercive condition in Experiment 2: the instruction that the commander sent by pressing one of two keys was either fully predictable from the key pressed (coercive predictable condition) or only predictable on 50% of trials (coercive unpredictable condition). Previous studies have showed that unpredicted outcomes reduce SoA [ 33 ] and should thus constitute a ceiling effect in the reduction of agency.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have examined the temporal decrease (or enhancement) of SoA. Di Costa et al investigated the SoA of rewards during the performance of an adaptation task and observed that the SoA involved an enhanced reward system [ 32 ]. Based on the above discussions, positive emotion driven by the reward system may have enhanced the SoA.…”
Section: Discussionmentioning
confidence: 99%